PENGARUH EKSTRAK ETANOL DAUN JALOH (Salix Tetrasperma Roxb) TERHADAP PERSENTASE PARASITEMIA PADA MENCIT (Mus musculus) YANG DIINFEKSI Plasmodium berghei - Nuzul Asmilia; Sugito Sugito; Erdiansyah Rahmi; Niko Febrianto (Jurnal Kedokteran Hewan, 2010)
This study aimed to verify the effect of ethanol extract of jaloh leaves at various doses on parasitemia percentage of in mice (Mus musculus), wich inoculated Plasmodium berghei. This study used 12 male mice (Mus musculus) strains Balb / C with average body weight of 30.2 grams of 2-month-old. This research using Completely Randomized Design (CRD) with four treatments and three replications. All the mice were infected with Plasmodium berghei prior to treatment on three days post infected the mice in group 2,3 and 4 were given with extract ethanol jaloh leaves at dose 50, 100, 150 mg/kgbw inspectively. The mice in group 1 (K0) were not given anything and consident as control.Observations parasitemia percentage using microscopy on preparations stained thin blood smear Giemsa. The parasitemia percentage data were analyzed using one way ANOVA. On the average (±SD) percentage of parasitemia during the three days in four treatments (K0, K1, K2, and K3) on the first day were 24.87±1.86; 24.33±1.53; 24.20±1.06; and 24.93±1.01. On the second day were 22.67±2.52; 23.00±1.00; 22.80±1.20; and 24.13±2.01; and on the third day were 24.77±1.66; 22.97±3.76; 21.13±1.90; and 24.27±1.42. Statistical analysis showed that ethanol extract of the jaloh leaves for KO, KI, KII, and KIV respectively treatment did not affect the percentage of parasitemia in mice (Mus musculus) inoculated Plasmodium berghei.